Ledermix Pulp treatment in a permanent molar: A case report - Fahd AA Karima; Asma Sultana; Tazdik G Chowdhury; Md Samsul Alam; Mohammed Wahiduzzaman (Update Dental College, 2014)
This case report describes the Indirect Pulp Treatment (IPT) of deep carious lesion in a permanent molar with Ledemix. A 18 years old male patient reported discomfort associated with thermal stimulation on the mandibular right first permanent molar. Radiographically revealed a deep buccal carious lesion, very close to the pulp. periapical radiolucency and periodontal space thickening was absent. Pulp sensitivity was confirmed by thermal pulp vitality tests. Based on the main complaint and the clinical and radiographic examinations, the treatment plan was established to preserve pulp vitality. Clinical procedures consisted of removing the infected dentin and lining the caries-affected dentin with ledermix cement, the tooth was restored with composite cement. After 12 month follow-up, no clinical or radiographic pathological findings were found. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21164 Update Dent. Coll. j: 2014; 4 (1): 31-37